Path assessment based network admission control algorithm - QIU Gong-an1; XU Chen1; ZHANG Guo-an1; BAO Zhi-hua1 (Tongxin xuebao)
The local link state metrics were measured by scheduler.At the same time,the stale path state metrics could be got from the router.The basic probability assignment functions of above metrics were described by the fuzzy state variableness.The path situation and the corresponding probability could be computed through data fusion based on Dempster rule.Then the path situation with the maximum probability would be regarded as the quasi-real-time path state.Network admission decision was made based on the estimated path state.Simulations show that the link utility of proposed policy has twice as the budget based network admission control under the similar blocking rate.And the complexity of network mechanism can be decreased by adding pre-computed at the edge to achieve coreless status in multi-hop networks.